Electrical-mechanical coupling performance of gallium arsenide under nanoindentation. (21st October 2020) - Xu, Lixia; Kong, Lingqi; Liu, Sihan; Wang, Shunbo; Zhao, Hongwei
Abstract: In this research, the electrical-mechanical coupling performance of gallium arsenide (GaAs) crystalline has been investigated by carrying out the in situ electrical measurement experiments which enabled us to record precisely both the mechanical behavior of the nanodeformed GaAs and the accompanying electrical response during nanoindentation. An effective and precise In situ electrical measurement system has been set up by introducing a conductive diamond indenter and both traditional and cyclic nanoindentation experiments have been performed. The experimental results showed that the application of indentation force caused a significant increase in the current flow due to the pressure-induced metallic phase transition of GaAs, and the magnitude of current flow was increased with increasing either the applied force or voltage. Furthermore, the current flow showed symmetric changes with the indentation loading and unloading, indicating a fully reversible metallic phase transformation of GaAs in indentation. On the other hand, the externally applied voltage (electrical field) was observed to barely affect the indentation force-depth curve (mechanical performance) of GaAs in respect of Young's modulus and hardness.